Patient-ventilator asynchrony as a predictor of weaning failure in mechanically ventilated COPD patients - Sadek, Samiaa H. (Egypt J Bronchol, 2021)
BACKGROUND: Patient-ventilator asynchrony is a common problem in mechanically ventilated patients. It is associated with adverse effects including increased work of breathing, patient discomfort, increased need for sedation, prolonged mechanical ventilation, weaning difficulties, and weaning failure. The purpose of the present was to describe patient-ventilator asynchrony and its impact on weaning outcomes in mechanically ventilated chronic obstructive pulmonary disease (COPD) patients. RESULTS: One hundred mechanically ventilated COPD patients were enrolled in this prospective study. Weaning failure (need of NIV or reintubation within 48 h) was noticed in 27 (27%) patients while 73 (73%) patients had successful weaning. Patients with failed weaning had significantly higher asynchrony index (A.I) and ineffective trigger index (ITI) in comparison with those with successful weaning (7.69 ± 3.71, 3.46 ± 2.59 versus 6.27 ± 3.14, 2.47 ± 2.08, respectively; P value< 0.04). Data were expressed as mean ± standard deviation. CONCLUSION: High asynchrony index and high ineffective trigger index may be early predictors of weaning failure in mechanically ventilated COPD patients.